Identidades e práticas culturais juvenis : as repúblicas estudantis de Ouro Preto - Souza, Eder Claudio Malta (2010)
The historic and patrimonial city of Ouro Preto, Minas Gerais/Brazil, has a strong characteristic of youthful university life, like other historic towns such as Coimbra, Portugal. The presence of the University printed new habits and forms of urban cultures, marked by the installation of the houses of students. This work, resulting from research conducted within the Center for Graduate Studies and Research in Social Sciences, Federal University of Sergipe, it is proposed to discuss these youthful sociability, in order to observe the cultural practices of the University of Ouro Preto. We analyze how the different identities appropriate the urban space and enunciate different lifestyles, pointing out places in this city. Our argument is that both the university and certain republics of the city spaces can be characterized as hybrid spaces or fragmentary, to enunciate that uses the locus of social change into public. The empirical comprises both traditional republics - are limited to the assets of the old town area of Ouro Preto - for new dwellings that have arisen in non central city, as well as streets and squares in which cultural manifestations are observed typical urban youth culture. What follows, as analytical suggestion is that the strong enrollment social and simbolic that culture gives to everyday urban life of Ouro Preto is a city space dissonant identity of different social practices and sociability.